Comparison of Single Dose Intravitreal Triamcinolone and Bevacizumab for the Visual Outcome and Complications in The Treatment of Refractory Diabetic Macular Edema - Sağdık, Hacı Murat; Alpay, Atilla; Uğurba&#, Sılay Cantürk; Büyükuysal, Mustafa Çağatay; Uğurbaş, Suat Hayri (Fırat University, 2012)
Objective: To compare the results of intravitreal triamsinolone (IVTA) and intravitreal bevacizumab (IVBE) injection for visual acuity and complications in treatment of diabetic macular edema (DMO). Materials and Methods: Sixty–two eyes of 62 patients were included in this study. The patients randomized in two groups and into 31 eyes, 4 mg/0.1 ml IVTA and into other 31 eyes 1.25 mg/0.05 ml IVBE were injected. The mean ages in IVTA and IVBE groups were 64±10 and 61.68±9.1 years respectively. Two groups were compared for the visual acuity changes, intraocular pressures changes and anterior and posterior segment complications. Results: The mean visual acuity increased significantly at 1 and 3 months when compared with preinjection values in the both groups. There was no statically difference between groups for pre and postoperative visual acuity. Any vision–threatening complications were not observed during follow–up examinations in both groups. Conclusion: For the treatment of DMO, 4 mg/0.1 ml IVTA and 1,25 mg/0.05 ml IVBE injections were found to be effective and safe methods and there was no statistically significant difference between groups in terms of effectiveness and complications.

Amaç: Diyabetik maküla ödemi (DMÖ) tedavisinde intravitreal triamsinolon asetonid (İVTA) ve intravitreal bevacizumab (İVBE) uygulamalarını görme düzeyi ve komplikasyonlar açısından karşılaştırmak. Gereç ve Yöntem: Altmış iki hastanın 62 gözü çalışma kapsamına alındı. Hastalar iki eşit gruba ayrılarak 31 göze 4 mg/0,1 ml İVTA, diğer 31 göze de 1.25 mg/0.05 ml İVBE enjekte edildi. İVTA grubunun ve İVBE grubunun yaş ortalamaları sırasıyla 64±10 yıl ve 61,68±9,1 yıl idi. İki grup görme düzeyleri değişimi, göz içi basınç değişimi, ön ve arka segment komplikasyonlar açısından birbiriyle kıyaslandı. Bulgular: Her iki grupta da ortalama görme keskinliği, enjeksiyon öncesi değerlerle karşılaştırıldığında,1. ve 3. aylarda anlamlı olarak artmıştı. Gruplar arasında görme düzeyleri açısından enjeksiyon öncesi ve sonrasında anlamlı bir fark yoktu. Her iki grupta da kontrol muayeneleri esnasında görmeyi tehdit eden bir komplikasyona rastlanmadı. Sonuç: DMÖ tedavisinde 4 mg/0,1 ml İVTA ve 1,25 mg/0.1 ml İVBE enjeksiyonu etkili ve güvenli metotlar olarak bulunmuşlardır ve gruplar arasında etkinlik ve komplikasyonlar açısından anlamlı fark gözlenmemiştir.
Dirençli Diyabetik Maküla Ödemi Tedavisinde Tek Doz İntravitreal Triamsinolon ve Bevacizumab'ın Görme Düzeyi ve Komplikasyonlar Açısından Karşılaştırılması